2022
DOI: 10.4236/jacen.2022.111002
|View full text |Cite
|
Sign up to set email alerts
|

Study of Biological Activity and Toxicity of Thiosemicarbazides Carbohydrate Derivatives by <i>in Silico</i>, <i>in Vitro</i> and <i>in Vivo</i> Methods

Abstract: Computer analysis of N-(β-D-galactopyranosyl)-thiosemicarbazide compounds by in silico method revealed high probability of antibacterial (antimycobacterial), anti-tuberculosis (antituberculosic), antiviral (Influenza), antitumor (antineoplastic) 9 > Pa > 0.5 and with a low probability of cytotoxic/cytostatic (cytostatic/cytotoxic) activities. An experimental study by in vitro and in vivo methods allowed us to conclude that studied new synthetic compound N-(β-D-galactopyranosyl)-thiosemicarbazide in the studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The demonstrated MIC value against two strains of S. aureus was similar to that demonstrated by our compounds and was in the range of 64–256 μg/mL [ 19 ]. D. Bhakiaraj et al, in a study from 2021 also showed the potential of compounds from the group of thiosemicarbazides with tetrazole ring against strains belonging to S. aureus [ 17 ]. In 2022, Halit Muğlu et al, published a study on the antibacterial activity of compounds from the 1,3,4-thiadiazole group with thiophene moiety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The demonstrated MIC value against two strains of S. aureus was similar to that demonstrated by our compounds and was in the range of 64–256 μg/mL [ 19 ]. D. Bhakiaraj et al, in a study from 2021 also showed the potential of compounds from the group of thiosemicarbazides with tetrazole ring against strains belonging to S. aureus [ 17 ]. In 2022, Halit Muğlu et al, published a study on the antibacterial activity of compounds from the 1,3,4-thiadiazole group with thiophene moiety.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, scientists have been interested in the use of small organic molecules, including heterocyclic compounds, as promising therapeutic substances [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Literature data from our review indicate that 1,3,4-thiadiazole derivatives and intermediates in their synthesis, 1,4-disubstituted thiosemicarbazides, are commonly reported as promising antimicrobial agents [ 1 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Compounds containing these structures often show higher activity than standard antibacterial drugs, such as penicillin [ 10 ].…”
Section: Introductionmentioning
confidence: 99%